Experimental research of multiple perfobond connectors for composite girders. (13th September 2017) - Neto, C.; Costa‐Neves, L. F.; da S. Vellasco, P. C. G.; Jordão, S.; Ihaddoudene, A. N. T.
ABSTRACT: Extensive research has been carried out in recent years focusing on the behaviour of innovative connectors for steel and concrete composite girders. Those elements exhibit large resistance and adequate behaviour under different load types, and at the same time are easy to fabricate and to erect on site. Among these types, the Perfobond connector or Perfobond rib, consisting of a perforated steel plate welded to the steel beam flange, has been extensively studied by numerous authors, due to its particularly convenient efficiency, behaviour and ductility characteristics. Although many connector types have been studied in the past, few studies focused on the behaviour of groups of special connectors, a typical arrangement used in conventional headed stud connectors. This paper focuses on the behaviour of multiple Perfobond connectors placed side‐by‐side on a steel girder and immersed in the reinforced concrete slab. This quite innovative arrangement enhances the resistance from a single connector classic layout, but the proximity to other connectors may significantly change the behaviour of individual connectors that interact with each other. Fourteen push‐out tests on groups of Perfobond connectors were carried out at the Civil Engineering Department of the University of Coimbra, Portugal, while this paper reports and discuss the results. The investigated variables were: the number of connectors, ranging from one (the basic arrangement) to three; the spacing between connectors; the transverse reinforcement within the connector's holes; and the concrete strength. The results are presented and discussed concentrating on the connector's structural response for shear transfer capacity, ductility and collapse modes. A comparative assessment of these properties focusing on the number of connectors and its spacing is presented and discussed, aiming at establishing preliminary conclusions about the behaviour of Perfobond groups. In addition, a brief comparison of the experimental results with existing analytical models for Perfobond connectors is also presented to establish the most convenient model for this particular geometry. Finally, some adapted models referred in the literature to cope with Perfobond groups are applied to the tested geometries and the analytical and experimental tests are compared and discussed.